KEPASTIAN HUKUM ATAS SURAT KETERANGAN BEBAS PAJAK PENGHASILAN ATAS HARTA WARIS TANAH DAN/ATAU BANGUNAN - TAJIB, EDDY; ISMAN, ALI YUS; TEGUH, STEVEN (Jurnal HUKUM BISNIS, 2026)
Legal certainty is one of the fundamental principles in the implementation of the taxation system in Indonesia, especially with regard to the collection of Income Tax (PPh) on the transfer of land and/or building rights. In practice, inherited assets in the form of land and buildings often cause doubts for the heirs. This is because although normatively inheritance is not included as an Income Tax object, the process of transferring rights still requires an Income Tax Exemption Certificate (SKB) issued by the Directorate General of Taxes. The SKB functions as an important instrument that ensures the transfer of inherited property is free from tax obligations and provides a guarantee of legal certainty for the heirs in obtaining rights to the heir's property. This research uses a normative legal research method with a statutory approach and a conceptual approach. The statutory approach is taken through a study of the Income Tax Law, Minister of Finance Regulations, and Director General of Taxes Regulations governing the requirements and procedures for the issuance of SKB PPh. Meanwhile, the conceptual approach is used to explain the meaning of legal certainty and the position of SKB as a means of protecting taxpayer rights in the context of the transfer of inherited property. Keywords: Legal Certainty, Exemption Certificate, Income Tax, Inherited Assets